Evaluating the Effectiveness of a Nursing Self-Management Module in Enhancing Clinical Self-Competency Among Nursing Students: Pengaruh Nursing Self Management Competency Module Terhadap Penerapan Self Competency Mahasiswa Perawat Praktik Klinik - Sri Handayani, Dwi; Ariyani Rokhmah, Noor (Infomasi dan Promosi Kesehatan, 2025)
Nursing competence refers to the ability and skills of nurses to understand others and handle various situations, including the ability to assess, communicate, and provide care. Competencies exist at different levels for nursing students in clinical practice. The study aims to determine the effect of the nursing self-management competency module on the implementation of self-competency in clinical practice nursing student. The research employed a quasi-experimental design with a pretest-posttest control group design. The research variables included the nursing self-management competency module and self-competence in maternity clinical practice. The sample was obtained through purposive sampling and divided into two groups: an intervention group and a control group, each consisting of 15 nursing students undergoing clinical practice. The intervention group received the nursing competency management module, while the control group followed routine formal procedures in the clinic. Data analysis was using the Mann-Whitney. The results showed that the majority of respondents in the control group had sufficient pretest competence, with 14 (93.3%) achieving this level, and the majority in the posttest also had sufficient competence, with 13 (86.7%). In contrast, the intervention group had sufficient pretest competence with 8 (53.3%) and high posttest competence with 11 (73.3%) with a p-value of 0.037, indicating that there is a significant effect of the nursing self-competency management module on the application of self-competency among nursing professional students during hospital maternity clinical practice. Conclusion: The nursing self-competency management module has a positive effect on the application of self-competency among nursing professional students during clinical practice.